Physical Self-Concept of Adolescents in Western Balkan Countries: A Pilot Study. Issue 2 (October 2014) - Janić, Snežana Radisavljević; Jurak, Gregor; Milanović, Ivana; Lazarević, Dušanka; Kovač, Marjeta; Novak, Dario
The aim of this study was to explore physical self-concept of adolescents of the Western Balkans (Serbia, Slovenia, Croatia, and Bosnia and Herzegovina) according to sex and country. The participants were 2, 606 students, ages 13 and 14 years ( M = 13.5, SD = 0.9). The Physical Self-Description Questionnaire (PSDQ) was used to assess multidimensional physical self-concept. The results show the interaction of sex and country for three dimensions of physical self-concept (Appearance, Global Physical Self-Concept, and Self-Esteem). It was shown that female and male adolescents' perception of physical appearance, self-esteem, and global physical self-concept is more susceptible to influences of socio-cultural factors in the monitored countries. In all other dimensions of Physical self-concept, sex differences were consistently manifested in favour of male adolescents, except in Flexibility. Regardless of adolescents' sex, under the increasing influence of Western culture in the Western Balkan countries, adolescents more critically evaluate their body and motor abilities.